Mining the chemical diversity of the hemp seed (Cannabis sativa L.) metabolome: discovery of a new molecular family widely distributed across hemp - Padilla-González, Guillermo Federico; Rosselli, Abigail; Sadgrove, Nicholas J.; Cui, Max; Simmonds, Monique S.J. (Frontiers in Plant Science, 2023)
Hemp (Cannabis sativa L.) is a widely researched industrial crop with a variety of applications in the pharmaceutical, nutraceutical, food, cosmetic, textile, and materials industries. Although many of these applications are related to its chemical composition, the chemical diversity of the hemp metabolome has not been explored in detail and new metabolites with unknown properties are likely to be discovered. In the current study, we explored the chemical diversity of the hemp seed metabolome through an untargeted metabolomic study of 52 germplasm accessions to 1) identify new metabolites and 2) link the presence of biologically important molecules to specific accessions on which to focus on in future studies. Multivariate analysis of mass spectral data demonstrated large variability of the polar chemistry profile between accessions. Five main groups were annotated based on their similar metabolic fingerprints. The investigation also led to the discovery of a new compound and four structural analogues, belonging to a previously unknown chemical class in hemp seeds: cinnamic acid glycosyl sulphates. Although variability in the fatty acid profiles was not as marked as the polar components, some accessions had a higher yield of fatty acids, and variation in the ratio of linoleic acid to α-linolenic acid was also observed, with some varieties closer to 3:1 (reported as optimal for human nutrition). We found that that cinnamic acid amides and lignanamides, the main chemical classes of bioactive metabolites in hemp seed, were more concentrated in the Spanish accession Kongo Hanf (CAN58) and the French accession CAN37, while the Italian cultivar Eletta Campana (CAN48) demonstrated the greatest yield of fatty acids. Our results indicate that the high variability of bioactive and novel metabolites across the studied hemp seed accessions may influence claims associated with their commercialization and inform breeding programs in cultivar development.